Radiosynthesis and ex vivo evaluation of [18F]-(S)-3-(6-(3-fluoropropoxy)benzo[d]isoxazol-3-yl)-5-(methoxymethyl)oxazolidin-2-one for imaging MAO-B with PET. Issue 2 (15th January 2015) - Hicks, Justin W.; Sadovski, Oleg; Parkes, Jun; Houle, Sylvain; Hay, Bruce A.; Carter, Randall L.; Wilson, Alan A.; Vasdev, Neil
Graphical abstract: Abstract: Carbon-11 labeled SL25.1188 (( S )-5-(methoxymethyl)-3-(6-(4, 4, 4-trifluorobutoxy)benzo[ d ]isoxazol-3-yl)oxazolidin-2-one) is a reversible radiotracer for monoamine oxidase B that was recently evaluated in healthy volunteers by positron emission tomography (PET). Herein we report the preparation and ex vivo evaluation of a fluorinated SL25.1188 derivative as a candidate 18 F-labeled PET radiotracer. ( S )-3-(6-(3-fluoropropoxy)benzo[ d ]isoxazol-3-yl)-5-(methoxy methyl)oxazolidin-2-one (1 ) was labeled with fluorine-18 in 51% uncorrected radiochemical yield having high radiochemical purity (>98%) and specific activity (109 ± 26 GBq/μmol). Ex vivo biodistribution studies demonstrated low radioactivity retention, specific binding and metabolic stability within rat brains. High uptake of radioactivity in bone is consistent with metabolic defluorination. In vitro binding assays of longer chain fluoroalkoxy derivatives revealed that the length of the carbon chain is an integral feature in MAO-B inhibitor potency and selectivity within this scaffold.